Church of Rome and the Condemnation of Nestorios of Constantinople during the Third Ecumenical Council - Gratsianskiy, Mikhail Viacheslavovich (Antičnaâ drevnostʹ i srednie veka, 2023)
This article researches the ecclesiastical and political processes at the first stage of the Third Ecumenical Council in Ephesus in late June – early July 431, which ended with the conciliar condemnation of Patriarch Nestorios of Constantinople. The comparative critical analysis of the acts of the Third Ecumenical Council allows the author to analyse the role of Pope Celestine I in the said process, who sent his legates to the Council. The article mainly examines the acts of the council sessions on July 10–11, 431, which reflect the participation of the newly arrived Roman legates in the work of the Council. A special analysis has been made of the documents presented by the papal representatives: the personal message of Pope Celestine to the Council and his instructions given to the legates. Particular attention has been paid to the analysis of the statements the legates made at the sessions, as these have important ideological contents, reflecting the “apostolic see’s” vision of its place among the local Churches and the limits of papal jurisdiction. Additionally, the procedural aspects associated with the adoption by the Council of both the papal legates themselves and the position of the Roman see voiced by them in regard to Nestorios condemnation issue have been studied and described. However, the way the Council participants, including the Council’s chairman, Cyril of Alexandria, and other leading bishops, were reacting to the statements of the legates, has also been studied. The author has made the conclusion that, despite the declarations of papal primacy and principality in matters of ecclesiastical justice voiced by the legates, the Council did not recognize the papal leadership and undertook a number of procedural measures, as well as the final communiqué, to demonstrate the equal position of the Roman bishop among other bishops of the Roman Empire represented at the Council.